Comparison of prolonged intubation and tracheostomy in pediatric intensive care unit among patients suffering from GB syndrome (Journal of Fatima Jinnah Medical University, 2018)
Background: Tracheostomy is often carried out in seriously sick patients for the ventilation. However, the importance of tracheostomy in ICU (intensive care unit) patients in terms of weaning from mechanical ventilation and outcomes remain controversial when compared with prolonged intubation. The study was carried out in patients of Guillian Barre Syndrome (GBS) to evaluate whether tracheostomy compared to prolonged intubation, minimizes the period of ventilation, ICU stay and mortality. Methods: A case control study was carried out between two groups of (GBS) patients who required mechanical ventilation. The study lasted 3 years (January 2008 to December 2010) and involved 40 patients who were splitted into 2 groups: the Tracheotomy Group (TG, n=20), where a tracheotomy was carried subsequent to the initial phase of tracheal intubation; and the Intubation Group (IG, n=20), in which intubation was kept on all the way to the period of hospitalization till discharge or death. Both the groups were similar in age and sex. We observed the entire period of ventilation in addition to the mean extent of hospital stay in the ICU and the death rate. Results: There was no significant statistical reduction in the length of mechanical ventilation for the TG: (24 ± 8.08 days) days compared to the IG: (37.30 ± 11.58 days) days (p=0.185). There was no significant difference in complications (p=0.165) and mortality (TG 15 % vs. IG 20 %; p = 0.677) between the two groups. Conclusion: No statistical difference in ventilation duration, hospital stay and mortality was found between tracheostomy and intubation groups.
Keywords: mechanical ventilation, tracheostomy, prolonged intubation